THE INFLUENCE OF PACKAGING, VARIATION, AND PRICE PERCEPTION ON THE PURCHASE DECISION OF TRADITIONAL MEDICINE - Ratna Ekasari; Rika Putri Setianingrum; Rezki Aulia Pramudita (Ecopreneur.12, 2022)
Traditional medicine is a conventional concoction of drinks because herbal medicine has been known for generations since the time of our ancestors before knowledge related to modern medicine entered. The impact of progress and intense competition, this study aims to analyze the effect of packaging, variety, and price on purchasing decisions of Jammu Biola Herbal in Sidoarjo Regency. The variables used are packaging (X1), type (X2), price (X3), and purchase decision (Y). This research uses quantitative methods. The data collection method used in this research is the questionnaire method. The data analysis method used is multiple linear regression analysis.